Nonpolar microporous Metal-Organic framework decorated with multiple functional sites for efficient Ethane/Ethylene separation - Zhu, Zhenliang; Xiao, Jianfei; Zhang, Min; Wang, Yuan; Xin Yao, Ke; Yuan, Shaojun (Separation and purification technology, 2025)
Nonpolar pore environments with multiple O/N/F active sites in a microporous MOF (Zn-IPA-F-dmtrz) were created for high-performance ethylene purification. [Display omitted] •A novel C2H6-selective microporous Zn-IPA-F-dmtrz MOF was synthesized for C2H4/C2H6 separation.•Zn-IPA-F-dmtrz integrated low-polarity aromatic rings and multiple O/N/F binding sites for C2H6.•Zn-IPA-F-dmtrz delivered a superior C2H6 capacity of 4.6 mmol/g and C2H6/C2H4 selectivity of 2.3.•Zn-IPA-F-dmtrz realized ultrapure C2H4 production in one-step breakthrough under dry and wet conditions. Efficiently achieving one-step adsorption separation of ethylene (C2H4) from ethane (C2H6) is a highly sought-after yet challenging task in the petrochemical industry. This underscores the need for enhanced standards in designing functional groups to formulate physisorbent materials with exceptional C2H6 trapping capacity, high C2H6/C2H4 selectivity, and material stability. In this study, we introduced a novel C2H6-selective microporous MOF (Zn-IPA-F-dmtrz), characterized by a nonpolar pore surface decorated with distinct advantageous O/N/F binding sites, creating a specialized nano-trap for C2H6, thereby enabling high-purity C2H4 production from C2H6/C2H4 mixtures. The synthesized Zn-IPA-F-dmtrz exhibited a remarkable C2H6 capacity of 4.6 mmol/g, coupled with an excellent C2H6/C2H4 selectivity of 2.3 at 298 K and 1 bar, outperforming the performance of many top-ranking adsorbents reported in recent years. Molecular simulation further demonstrated multiple synergistic interactions between this framework and C2H6. Moreover, breakthrough experiments confirmed the good stability of Zn-IPA-F-dmtrz, indicating its effectiveness in separating C2H6/C2H4 mixtures even under high-humidity conditions. This work provides valuable insights into how purposeful functionalization of nonpolar pore surfaces contributes to the construction of MOF materials tailored for highly efficient C2H6/C2H4 separation applications.